2015
DOI: 10.1016/j.enggeo.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the barrier effect caused by underground constructions on porous aquifers with low hydraulic gradient: A case study of the metro construction in Barcelona, Spain

Abstract: Construction of tunnels can impact aquifers because of the changes produced in the natural groundwater behavior. The drain effect, which is one of the most important impacts, can be eliminated using a tunnelboring machine (TBM) to drill a tunnel with an impervious lining. However, the use of impermeable linings results in aquifer obstruction, giving rise to the barrier effect, which may cause an increase and decrease of the hydraulic head upgradient and downgradient of the tunnel, respectively. This modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Note that the representativeness of the predictions performed using this numerical model are supported by other studies and projects developed regarding the construction of La Sagrera Railway Station (Pujades et al, 2012b;Font-Capo et al, 2015;Serrano-Juan et al, 2016;Culí et al, 2016).…”
Section: Calculation Of the Pumping Settlements (Numerical Model And supporting
confidence: 73%
See 2 more Smart Citations
“…Note that the representativeness of the predictions performed using this numerical model are supported by other studies and projects developed regarding the construction of La Sagrera Railway Station (Pujades et al, 2012b;Font-Capo et al, 2015;Serrano-Juan et al, 2016;Culí et al, 2016).…”
Section: Calculation Of the Pumping Settlements (Numerical Model And supporting
confidence: 73%
“…Regarding the Pliocene materials, the value of K of the fine materials (marls) ranges from 0.001 to 0.01 m/ d, and the value of K of the sands ranges from 0.1 to 10 m/d. These values were derived from the numerous hydraulic tests performed in the city of Barcelona during recent underground construction projects (Pujades et al, 2012b;Font-Capo et al, 2015;Serrano-Juan et al, 2016;Culí et al, 2016). Specifically, in the study site, the pumping tests undertaken before the start of the construction projects showed that the minimum and maximum hydraulic conductivity is 0.001 m/d and 700 m/d, respectively.…”
Section: Geographical Geological and Hydrogeological Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tectonic-structural terms, such structures as grabens and horsts can influence the aquifer geometries by controlling the space for sedimentary deposition of further saturated bodies (Díaz et al 2014). In addition, faults and artificial structures also play important roles in permeability, acting either as a barrier slowing the flow of water or as conduits between aquifers (e.g., Pujades et al 2012, Font-Capo et al 2015. Although the relationship between faults and aquifer geometry has already been established for several areas, such as southern California, USA (Landon et al 2015) and southeastern Tunisia (Chihi et al 2015), more study cases are needed to fully understand the role of faults on aquifer properties.…”
Section: Introductionmentioning
confidence: 99%
“…During the metro construction in karst areas, caves that have developed or are developing are often encountered, which pose great difficulties in tunneling by shield machine. As most of the karst caves are in non-filled, semi-filled, or rich muddy water-filled, a number of hazards including sink holes, karst collapse, and water inrush can easily occur in metro tunnel projects when they pass through karst areas [17,18].…”
Section: Introductionmentioning
confidence: 99%